The IMF's Statistical Systems in Context of Revision of the United Nations' A System of National Accounts - Galbis, Vicente (Washington, D.C. : International Monetary Fund, 1991)
Sponsored by the IMF's Statistics Department and edited by Vicente Galbis, this volume contributes to the international discussion that resulted in the UN's "A System of National Accounts, 1993." Experts from the IMF, UN, OECD, EC, and statistical institutions examine issues pertaining to external sector transactions, public sector accounts, and financial flows and balances.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet